Preparation and application of Nb2O5 nanofibers in CO2 photoconversion. - PRADO, A. C. F. (2022)
Increasing global warming due to NOx, CO2, and CH4, is significantly harming ecosystems and life worldwide. One promising methodology is converting pollutants into valuable chemicals via photocatalytic processes (by reusable photocatalysts). In this context, the present work aimed to produce a Nb2O5 photocatalyst nanofiber system by electrospinning to convert CO2. Based on the collected data, the calcination at 600 ◦C for 2 h resulted in the best condition to obtain nanofibers with homogeneous surfaces and an average diameter of 84 nm. As a result, the Nb2O5 nanofibers converted CO2 mostly into CO and CH4, reaching values around 8.5 µmol g−1 and 0.55 µmol g−1, respectively.